STRATEGI PEMASARAN BATIK LABAKO UD. BINTANG TIMUR DI DESA SUMBERPAKEM KECAMATAN SUMBERJAMBE KABUPATEN JEMBER - Hayik Heditullah; Retna Ngesti Sedyati; Sukidin Sukidin (Economic Education, University of Jember, 2017)
This study aims to describe how the marketing strategy of batako labako done UD. Bintang Timur in Sumberpakem village Sumberjambe district Jember district. The type of research used in this study is qualitative. Place of study is determined by purposive area, that is Sumberpakem village Sumberjambe Sub district Jember. Informants used in this study are owners and employees. The Eastern Star will provide the information needed by the researcher. Furthermore, the additional informant in this research is the buyer or customer or agent of UD. Bintang Timur. The data in this study were obtained by document, interview and observation. Data analysis used in this research is data reduction, data presentation, and withdrawal conclusion done interactively and continuously. The end result of this research can be concluded that in selling or marketing its products, this company uses marketing strategy by focusing on promotion or promotion, in which related to advertising, sales promotion, and personal selling. First on the process of advertising is used two kinds of media that is, using the brochure media in spread or given to the community for free, and through the media business cards given to buyers or prospective buyers directly ditoko UD. Bintang Timur. Both sales promotions are made by this company through trade shows, product displays, purchase pieces. And the third personal sale is done by displaying his batik products neatly in a storefront located in UD Bintang Timur.